Development and Experimentation of a New Mathematical Model for Teaching-Learning the Radioactive Decay Law - Adnane Mamane; Nadia Benjelloun (MDPI AG, 2019)
Our plan is to bring professors and their Moroccan pupils to focus on the teaching−learning of physics, without adopting forced mathematical modeling in previously unknown frames and registers, as is actually the practice. The preliminary study consists of developing a new analytical model for the teaching−learning of the radioactive decay law. However, the validation study was conducted to test its pertinence. The results show that, compared to the official model, pupils are very satisfied. In fact, the proposed new model intelligibility frame facilitates the linking of the concept of space of reality, with those of registers and frames. The pupils’ performance amounted to 65.33% in the development of the analytical model of the radioactive decay law, while in terms of suitable applications, pupil performance ranged from 0% to 75%. This result is partly due to the collaborative work, which induced a very significant increase in pupil performance. They were observed between increases ranging from 33.3% to 69.5%. In fact, we attribute these good performances to the ICT resources’ mobilization, specifically SimulP200, the one that we have exclusively elaborated. These resources have also mitigated the difficulties of the experiment, and those related to the processes of elaboration of different radioactive decay law model.